An assessment of mathematical communication competency of fourth year science and non-science high school students - Aman, Jocelyn P. (2006)
The levels of mathematical communication competency of science and non-science high school students were assessed and compared in this study. It also determined if performance in Mathematics and performance in English have significant relationships with the level of mathematical competency. The respondents were senior students from two intact sections of the fourth year class under the Special Science Curriculum and the SEDP Curriculum of a regional science high school. A combination of two-group posttest-only causal comparative and correlational research designs were used and the standardized Culture Fair Intelligence Test (CFIT) Scale 2 and the researcher-made Mathematical Communication Test (MCT) were employed. It was concluded that Science students have a higher level of Mathematical Communication Competence than Non-Science students and that the students' level of Mathematical Communication Competence has a significant positive relationship with performance in Mathematics and English.
Thesis (M.A. Mathematics Education)--University of the Philippines, Diliman.
Keywords: Mathematical ability -- Testing; Mathematics -- Study and teaching (Secondary) -- Philippines -- Central Mindanao; High school seniors -- Philippines -- Central Mindanao